Investigation of ground-motion spatial variability effects on component and system vulnerability of a floating cable-stayed bridge. Issue 8 (June 2019) - Ma, Kai; Zhong, Jian; Feng, Ruiwei; Yuan, Wancheng
The effects of ground-motion spatial variability on the seismic vulnerability of a floating cable-stayed bridge with 420-m long main span are investigated using component and system-level fragility analysis methods. Four combinations of the spatial variability components are considered including (a) the incoherence effect; (b) the incoherence and wave-passage effects; (c) the incoherence and site-response effects; and (d) general excitation case including the incoherence, wave-passage, and site-response effects. Parametric study was carried out to assess the sensitivity of seismic fragility to the variation of spatial variability components. The results indicate that the bridge becomes more vulnerable under spatially varying excitations than uniform excitations. The fragile components and the bridge system become more vulnerable with an increase in incoherence level. The component and system-level vulnerabilities are not sensitive to the variation of apparent wave velocities in most cases. However, the site-response effect is more complex than incoherence and wave-passage effects. There is no general trend about its effect on different components, whereas the system fragility increases as the soil conditions of adjacent excitation sites change more significantly and the soil types vary from the soft to the firm along wave-traveling direction. In addition, the bridge tends to be more vulnerable if the soil condition of the reference site becomes softer for the general excitation case. Spatial variability effects, especially incoherence and site-response effects, should be considered in the fragility analyses of this type of bridges.